Model Development of Children Under Mortality Rate With Group Method of Data Handling - Iing Lukman; M. N. Hassan; Noor Akma I; M. N. Sulaiman (International Journal of Engineering Science and Technology Development (IJEST), 2013)
in this research we examine aspects of the interdependence between economic development and the use of environmental and natural resources assets from global data published by united nations. for that purpose, we use data mining techniques.data mining techniques applied in this paper were: 1) group method of data handling (gmdh), originally from engineering, introducing principles of evolution - inheritance, mutation and selection - for generating a network structure systematically to develop the automatic model, synthesis, and its validation; 2) step wise regression were also applied for some cases.data sets for this research consist of one sets integration data of air quality data and macroeconomic data of the cross-country data of world development indicator 2003 (wdi 2003). the result shows that the mortality rate of children under five years old is dependent on sanitation and water facilities obtained from gmdh results. however, the results from step-wise regression shows that mortality rate was dependent on annual deforestation, particulate matter, nationally protected area, with the big contribution was from annual deforestation.